Edukasi Penyakit Tidak Menular (PTM) pada Warga Dusun II Desa Watas Marga Kabupaten Rejang Lebong Provinsi Bengkulu - Melia Rosvita Sari; Kasi Apiko Sari; Lilis Sundari; Apreni Apreni; Vina Ardiany; Nimas Ayu L.N (Jurnal Pakar Pengabdian Kesehatan, 2025)
Non-Communicable Diseases (NCDs) such as hypertension and diabetes mellitus remain major public health problems in Indonesia, particularly in rural areas with limited access to health information. Dusun II, Watas Marga Village, Rejang Lebong Regency, is one of the areas with increasing behavioral risk factors, including smoking habits, low physical activity, and unhealthy diet. This community service program aims to improve public knowledge regarding NCD prevention through structured education, demonstrations, and health screening. The activities consisted of counseling on hypertension and diabetes risk factors, proper dietary practices, physical activity guidelines, and early detection through blood pressure and blood glucose checks. Collaboration was carried out with village cadres and local health workers. The results showed an increase in public understanding regarding the importance of early detection, reduced sugar–salt–fat consumption, and lifestyle modification. Participants demonstrated improved awareness as indicated by the shift from “low” to “good” knowledge categories in the post-education assessment. This activity proved effective as a promotive and preventive strategy to reduce NCD risk at the community level. Sustainable education and cross-sector collaboration are needed to support long-term NCD prevention in Watas Marga Village.